Analysis of Key Genes Involved in Potato Anthocyanin Biosynthesis Based on Genomics and Transcriptomics Data - Tengkun, Nie; Dongdong, Wang; Xiaohui, Ma; Yue, Chen; Qin, Chen (Frontiers in Plant Science, 2019)
The accumulation of secondary metabolites such as anthocyanins in cells is an important cause of the colored plants. The synthesis and accumulation of anthocyanins are regulated by multiple genes, of which the R2R3-MYB transcription factor gene family plays an important role. Based on the genomic data in the PGSC and the transcriptome data in the SRA, this study used potato as a model plant to comprehensively analyze the plant anthocyanins accumulation process. The results indicated that the most critical step in the synthesis of potato anthocyanins was to make p-coumaroyl-CoA enter flavonoid biosynthetic pathway. The up-regulated expression of CHS gene and the down-regulated expression of HCT significantly promoted this process. At the same time, the anthocyanins in the potato were gradually synthesized during the process from leaves transport to tubers. New transcripts of stAN1 and PAL were cloned, named stAN1-like and PAL-like respectively, but the functions of these two new transcripts still need further study. In addition, the sequence characteristics of amino acids in the R2-MYB and R3-MYB domains of potato were preliminarily identified. The aim of this study is to find out the crucial major genes that affect anthocyanins biosynthesis through multi-omics joint analysis, transform quantitative traits into quality traits, which provides a basis and reference for the regulation of plant anthocyanin biosynthesis.